Developing Value-Integrated Paragraph Writing Materials For Enhancing EFL Students’ Multicultural Awareness - Tiara Emiarti; Nadrah Nadrah; Andriadi Andriadi (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This research aimed to identify students’ needs, design paragraph writing materials integrating religious moderation values, and examine the validity of the developed materials for promoting students’ multicultural awareness. This study employed a Research and Development (R&D) design adapted from Borg and Gall. The participants were second-semester students of the English Education Study Program (TBI) at UIN Fatmawati Sukarno Bengkulu. Data were collected through needs analysis questionnaires, semi-structured interviews, classroom observations, and expert validation sheets. The development process included needs analysis, instructional material design, expert validation, revision, and product finalization. The instructional materials were developed based on the process-based writing approach and integrated the values of religious moderation, including tawassuth (moderation), *tasamuh* (tolerance), and *i’tidal* (justice), to foster students’ multicultural awareness. The developed product consists of twelve instructional units covering paragraph organization, idea generation, paragraph development, mechanics, and various paragraph types enriched with contextual activities reflecting religious moderation values. The expert validation results indicated that the instructional materials met the criteria of validity in terms of content, language, instructional design, and the integration of religious moderation values, making them appropriate for use in paragraph writing instruction. The findings suggest that integrating religious moderation values into English writing materials provides contextual learning experiences that not only improve students’ paragraph writing skills but also promote tolerance, respect for diversity, and multicultural awareness. Therefore, the developed instructional materials can serve as an alternative resource for English language teaching, particularly in paragraph writing courses that emphasize both language competence and character development